The God of the Middle English Cleanness and His Erotic Exhortations of Purity - Spyra, Piotr (Studia Anglica Posnaniensia, 2013)
The Middle English Cleanness is a poem unique in the medieval context in that it couples its homophobic discourse with a powerful vindication of sexual pleasure and its role in relationships without referring to the procreative telos of marriage. In fact, Cleanness does not even stress that the only proper arena for erotic desire is the marriage bed, with the narrator emphasising the mutuality of pleasure instead. The article investigates the text’s rhetorical interplay between the vilification of homosexuals and the divine endorsement of heterosexual lovemaking. Going beyond the established critical consensus on the issue, it argues that the contrast between the two serves not only to allow the author to vent his homophobic prejudice but also connects with the epistemological concerns of Pearl, the text that precedes Cleanness in the Cotton Nero A.x manuscript.